Ethical considerations surrounding Voluntary Medical Male Circumcision (VMMC) in South Africa as an intervention for HIV prevention - May, Robyn Walker (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.